MOTIF HIAS NISAN: LATAR BELAKANG PEMBUATAN HIASAN LAMPU GANTUNG PADA NISAN DI BARUS - Repelita Wahyu Oetomo (Berkala Arkeologi Sangkhakala, 2017)
Tombstones in Barus, aside from consisting of various types, have an assortment of carved decorations on them. The method used in this research is retracing the meaning behind the chandelier decoration motifs through their types. Most probably, the types and decoration patterns of the tombstones have certain meanings, which symbolize the figures buried in the tombs. One of the decorating motifs quite frequently found on the tombstones of Barus is the chandelier motif, which is related to the figures buried in them, that is as guiding light in terms of religious teaching like depicted in 35 th verse of An Nur.Nisan di Barus selain terdiri dari berbagai tipe, pada nisan tersebut terdapat berbagai pahatan yang menghiasinya. Tipologi maupun pola hias dari nisan tersebut besar kemungkinan memiliki makna-makna tertentu yang merupakan simbolisasi dari tokoh yang dimakamkan. Salah satu pola hias yang cukup banyak didapati pada makam-makam di Barus adalah motif hias lampu gantung, hal ini dikaitkan dengan simbol dari tokoh yang dimakamkan, yaitu sebagai penerang dalam agama, seperti yang digambarkan dalam Surat An Nur ayat 35.